Relationship of Employee's Placement With The Employees’ Performance Faculty of Economics of Manado State University - Nancy Jenny Kaligis (AIBPM Publisher, 2018)
This research was conducted with the aim to find out how the relationship between the placement of employees and the performance of employees at the Economic Faculty of Manado State University. The method used in this research is descriptive method where this method can allow researchers to make connections between variables, test hypotheses, develop generalizations and develop theories that have universal validation. The ability of employees to suit the demands of work tasks, is one of the important factors to support the effectiveness and efficiency of organisms in achieving goals. The employee development program through appropriate training is a means to facilitate the employee's abilities, thus the employee's performance will be better so that the company's goals will be achieved. Thus, it can be concluded that the relationship between employee placement and employee performance is meaningful. In this case it is evidenced by the significance test where t count is greater than t table and employee placement will cause an increase in employee performance at the UNIMA Economics Faculty. Keywords: Employee Placement, Employee Performance, FE UNIMA